DETERMINING PRAYER TIMES IN MIDNIGHT SUN COUNTRIES - Salma, Aulia; As'ad, Muhammad (Fakultas Syari'ah dan Hukum UIN Walisongo, 2024)
The phenomenon of the midnight sun presents unique challenges for people living in countries that experience prolonged daylight. One issue in these regions is the application of iḥtiyāṭ (precautionary measures) in religious practices, such as determining prayer times and fasting hours according to Islamic teachings. This article explores the socio-religious implications of time management in countries experiencing the midnight sun phenomenon, focusing on its impact on Muslim communities. Through qualitative analysis of literature, case studies, and religious texts, this research examines the challenges faced by Muslims in fulfilling religious obligations amidst extended daylight hours. The study also investigates the responses and adaptations made by religious authorities and community members to address the scheduling of prayer times in countries with midnight sun. This research contributes to a deeper understanding of the intersection between natural phenomena, cultural traditions, and religious practices by highlighting this rarely discussed aspect of religious observance in regions with unique daylight patterns.